Enhancement of antibiotic activity by efflux inhibitors against multidrug resistant Mycobacterium tuberculosis clinical isolates from Brazil - Coelho, Tatiane; Machado, Diana; Couto, Isabel; Maschmann, Raquel; Ramos, Daniela; von Groll, Andrea; Rossetti, Maria L.; Silva, Pedro A.; Viveiros, Miguel (Frontiers in Microbiology, 2015)
Drug resistant tuberculosis continues to increase and new approaches for its treatment are necessary. The identification of M. tuberculosis clinical isolates presenting efflux as part of their resistant phenotype has a major impact in tuberculosis treatment. In this work, we used a checkerboard procedure combined with the tetrazolium microplate-based assay (TEMA) to study single combinations between antituberculosis drugs and efflux inhibitors (EIs) against multidrug resistant M. tuberculosis clinical isolates using the fully susceptible strain H37Rv as reference. Efflux activity was studied on a real-time basis by a fluorometric method that uses ethidium bromide as efflux substrate. Quantification of efflux pump genes mRNA transcriptional levels were performed by RT-qPCR. The fractional inhibitory concentrations (FIC) indicated synergistic activity for the interactions between isoniazid, rifampicin, amikacin, ofloxacin, and ethidium bromide plus the EIs verapamil, thioridazine and chlorpromazine. The FICs ranged from 0.25, indicating a four-fold reduction on the MICs, to 0.015, 64-fold reduction. The detection of active efflux by real-time fluorometry showed that all strains presented intrinsic efflux activity that contributes to the overall resistance which can be inhibited in the presence of the EIs. The quantification of the mRNA levels of the most important efflux pump genes on these strains shows that they are intrinsically predisposed to expel toxic compounds as the exposure to subinhibitory concentrations of antibiotics were not necessary to increase the pump mRNA levels when compared with the non-exposed counterpart. The results obtained in this study confirm that the intrinsic efflux activity contributes to the overall resistance in multidrug resistant clinical isolates of M. tuberculosis and that the inhibition of efflux pumps by the EIs can enhance the clinical effect of antibiotics that are their substrates.